Prediction of Ultimate Bearing Capacity of Cohesionless Soils Using Soft Computing Techniques. (5th December 2011) - Adarsh, S.; Dhanya, R.; Krishna, G.; Merlin, R.; Tina, J.
Abstract : This study examines the potential of two soft computing techniques, namely, support vector machines (SVMs) and genetic programming (GP), to predict ultimate bearing capacity of cohesionless soils beneath shallow foundations. The width of footing (B ), depth of footing (D ), the length-to-width ratio (L / B ) of footings, density of soil (γ or γ ′ ), angle of internal friction (Φ ), and so forth were used as model input parameters to predict ultimate bearing capacity (q u ). The results of present models were compared with those obtained by three theoretical approaches, artificial neural networks (ANNs), and fuzzy inference system (FIS) reported in the literature. The statistical evaluation of results shows that the presently applied paradigms are better than the theoretical approaches and are competing well with the other soft computing techniques. The performance evaluation of GP model results based on multiple error criteria confirms that GP is very efficient in accurate prediction of ultimate bearing capacity cohesionless soils when compared with other models considered in this study.